Biomechanical Kinetic Chain Analysis of Service Motion for Speed Ball Prediction Through SBM-03 App Development - Ricko Irawan; Bambang Priyono; Soedjatmiko Soedjatmiko; Imam Ciptaning Wahyu Santoso; Agung Wahyudi; Adi S (Physical Education Theory and Methodology)
Background. The kinetic chain of the serve stroke is a coordinated activation of body segments (legs, torso, shoulders, arms, and hands) that begins with the ground reaction force against the legs on the ground and ends with racket acceleration through the ball. The objective of this study is to place the end segment, hand, and racket in an optimal position at an optimal speed to "make the ball travel" as best as possible. The efficient use of the kinetic chain segment creates a much greater racket velocity than its parts. On the contrary, a broken kinetic chain makes the ball speed less optimal and can even lead to injury. However, the reality is that the kinetic chain movement and ball speed rate cannot be seen simply using the observation method. Thus, a specific technology is needed to diagnose it.